Pengambilan Keputusan Dalam Lingkungan Pendidikan (SD Negeri 083 Pidoli) Dan Lingkungan Non Pendidikan (Persatuan Naposo Nauli Bulung Pidoli Lombang) - Reni Septrisia; Siti Rodiah Lubis; Iqbal Alawi Hasibuan; Hidayatul Abror; Lanni Lubis; Fitri Padilah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is motivated by the leader's ability to make decisions in the field of education at SD Negeri 083 Pidoli and non-education at the Naposo Nauli Bulung Association, Pidoli Lombang Village. This research aims to see the difference between decision making in an educational environment and decision making in a non-educational environment in terms of the decision making process and the type of decision making. This research uses a descriptive method with a qualitative approach. This research data collection technique uses observation, interview and documentation techniques. The results of this research show that 1) there is a difference between decision making in the educational environment and non-educational decision making, the difference being that in the educational sphere the decision making made by the school principal is guided by government policy, while decision making in the non-educational environment is not guided by the government but is not violate government legal regulations. 2) supporting factors in decision making in both educational and non-educational environments are the commitment of all decision makers and users, support and cooperation as supporters. Meanwhile, the inhibiting factors are the indifference of fellow members in the decisions made and in terms of costs that do not support the decisions/programs made.